A design process for balanced educational video games with collaborative activities (2015)
The efficiency of educational video games could be improved through the use of a specific development method that allows them to keep both their educational and recreational goals and maintains their playability. Accordingly, we present a process for the incremental design of educational video games with collaborative activities based on Software Engineering principles. This process intends to make the specification and design of educational and recreational contents easier, and also ensures a balance between educational and playful components. To support this methodology, we present a pilot authoring tool that implements our design process.